Maqāṣid Al-Sharī‘ah: The Thoughts of Imam al-Shāṭibī in Tepung Tawar Ceremony at Melayu Traditional Marriage - Reza Fahlevi; Muslihun Muslihun (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
Tradition is a habit that people continuously carry out in a specific area. Carrying out traditions can be interpreted as realizing the process of socialization between each generation in a civilization. Each region has different traditions and cultures. One tradition still preserved from generation to generation by the people of Suka Maju Village is the Tepung Tawar ceremony. The purpose of this research is to critically examine the thinking of Imam al-Shāṭibī in Maqāṣid al-Sharī‘ah as an effort to measure the value of relevance between shariah and tradition; in this case, it is used to analyze the tradition of tepung tawar in traditional Melayu marriages in Suka Maju village. The results in this study indicate that the tradition of tepung tawar in the marriage of the Melayu community in Suka Maju Village, which was analyzed using Maqāṣid al-Sharī‘ah from the perspective of Imam Imam al-Shāṭibī is considered relevant, which is described on the validity and purpose of the procession. Furthermore, if based on the classification of Al-'awāid Imam al-Shāṭibī's idea to sharpen the analysis, then it strengthens that the tepung tawar tradition is the embodiment of Al-'awāid al-Jāriyyah’s conception of Al-shāṭibī. Tradisi merupakan kebiasaan yang secara kontinuitas dilakukan oleh masyarakat disuatu daerah tertentu. Melaksanakan tradisi dapat diartikan merealisasikan proses sosialisasi antar setiap generasi dalam sebuah peradaban. Setiap daerah mempunyai tradisi dan kebudayaan yang berbeda-beda. Salah satu tradisi yang masih terpelihara secara turun temurun oleh masyarakat Desa Suka Maju adalah upacara Tepung Tawar. Adapun tujuan dalam penelitiaan ini yaitu menelaah secara kritis pemikiran Imam al-Shāṭibī dalam Maqāṣid al-Sharī‘ah, sebagai upaya menakar nilai relevansi antara shariah dan tradisi, dalam hal ini digunakan untuk menganalisa tradisi tepung tawar pada perkawinan adat Melayu di Desa Suka Maju. Hasil dalam penelitian ini menunjukan bahwa tradisi tepung tawar pada perkawinan masyarakat Melayu di Desa Suka Maju yang dianalisa menggunakan Maqāṣid al-Sharī‘ah perspektif Imam al-Shāṭibī dianggap telah relevan, yang terdeskripsi pada keabsahan maupun tujuan prosesinya. Lebih lanjut, jika berdasarkan klasifikasi Al-‘awāid gagasan Imam al-Shāṭibī untuk mempertanjam analisa, maka memperkuat bahwa tradisi tepung tawar merupakan perwujudan Al-‘awāid al-Jāriyyah konsepsi Al-shāṭibī.